Eh-Sayyeh, Jordanien: Die Arbeiten des Jahres 2015 - Bartl, Karin; Kafafi, Zeidan (e-Forschungsberichte des DAI, 2023)
The Neolithic site of eh-Sayyeh in Northern Jordan covers more than 10 ha and is therefore designated as a mega site. Main settlement periods are attested for the 8th and 6th mill. calBC. During the investigations carried out in 2015 a completely intact oval building with stone cover was exposed, which showed no archaeological material inside. Typologically it reminds of late Neolithic graves. Therefore, this structure might hypothetically be interpreted as a grave which was never used.